The Evaluation of Changes in The Knee Meniscus in vivo at 3T MRI Scanner - Lenka Horňáková; Daniel Hadraba; Karel Jelen (Karolinum Press, 2015)
Noninvasive imagining of the knee meniscus without the use of the contrast agents is more difficult compared to articular cartilage. Despite the lower signal intensity of the knee meniscus, MRI is considered the best non-invasive imaging method. Thanks to the lower water content in the meniscus compared to the surrounding tissues, it can be distinguished from the environment, but the determination of the boundaries is more complicated than in articular cartilage. There are many studies dealing with the MR imaging of the loaded and also unloaded knee, but they have mainly observed quantitative and geometric changes (movement or deformation of tissue), not targeted qualitative changes in the extracellular matrix (ECM). These changes can be evaluated with T2 relaxation times, which are more sensitive to the interaction of water molecules and the concentration of macromolecules and structures of the ECM, especially in the interaction based on the content, orientation and anisotropy of collagen fibers. Fluid and tissues with the higher water content level have long relaxation time T2. In the healthy meniscus these times are shorter; the reason is a highly organized structure of collagen and lower content of proteoglycans. To quantitatively detect changes, it is necessary to assure a sufficiently high resolution of images throughout choosing appropriate pulse sequences. After that, the acquired data can be processed to produce the T2 maps, to portray non-invasive collagen content, architecture of the ROI, changes in the water content (distribution of interstitial water in the solid matrix) and the spatial variation in depth. The aim of this work is firstly to introduce the meaning of T2 relaxation and methods for calculating T2 relaxation times. Further, the aim of this work is to give a brief description of the current pulse sequences used to display menisci.